ANALISIS DAN MITIGASI RISIKO KESELAMATAN DAN KECELAKAAN KERJA PADA PROYEK PEMBANGUNAN BALI INTERCONTINENTAL GRAND BALLROOM - I GUSTI AGUNG AYU ISTRI LESTARI; NI LUH MADE AYU MIRAYANI PRADNYADARI; I KOMANG DWIKI ARI ANDITHA (Universitas Mahasaraswati K. Mataram, 2024)
In construction projects, work accident risk management plays a key role in maintaining employee safety and company performance. Management of work accident risks in the Bali Intercontinental Grand Ballroom construction project includes risk identification, risk analysis and risk mitigation measures aimed at reducing and avoiding risks. This research used qualitative methods involving interviews and questionnaires with 25 different respondents. The research results identified 40 relevant risks in the Bali Intercontinental Grand Ballroom development project. Of these risks, 39 were considered unexpected risks, while one risk was acceptable. Unexpected risks dominate in this project, and risk mitigation is tailored to the responsibilities of the Contractor and Planner. One of the highest risks is the lack of clear sanctions for companies that do not implement K3, and the solution is to impose sanctions on companies that violate K3 standards against their workers. This research provides important insights into occupational accident risk management in complex construction projects